2014
DOI: 10.1039/c3cp54273d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of the electronic properties of Cu-doped anatase TiO2

Abstract: A good correlation was obtained between the electronic properties of Cu-doped anatase TiO2 by virtue of both physical chemistry characterization and theoretical calculations. Pure and Cu-doped TiO2 were synthesized. The composition, structural and electronic properties, and the band gap energy were obtained using several techniques. The method of synthesis used produces Cu-doped anatase TiO2, and XRD, XPS and Raman spectroscopy indicate that Cu atoms are incorporated in the structure by substitution of Ti atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 91 publications
7
85
1
1
Order By: Relevance
“…Because of the negative shift of the XPS peaks of Ti 2p to a lower binding energy and the blue shift of the Eg Raman mode of TiO2, it is reasonable to conclude the slight formation of partially-reduced Ti species (Ti 4+ ) by the free electrons left from the oxygen vacancies formed in the CuO-TiO2 NTs. As can be seen in Figure 6a, it should be noted that the energy difference between the XPS Ti 2p3/2 and Ti 2p1/2 peaks for the CuO-TiO2 NTs (5.5 eV) is comparable to that of the pristine TiO2 nanotubes (5.4.eV), which confirms that the anatase phase is maintained upon CuO loading [48]. …”
Section: Metal-support Interactionssupporting
confidence: 59%
See 1 more Smart Citation
“…Because of the negative shift of the XPS peaks of Ti 2p to a lower binding energy and the blue shift of the Eg Raman mode of TiO2, it is reasonable to conclude the slight formation of partially-reduced Ti species (Ti 4+ ) by the free electrons left from the oxygen vacancies formed in the CuO-TiO2 NTs. As can be seen in Figure 6a, it should be noted that the energy difference between the XPS Ti 2p3/2 and Ti 2p1/2 peaks for the CuO-TiO2 NTs (5.5 eV) is comparable to that of the pristine TiO2 nanotubes (5.4.eV), which confirms that the anatase phase is maintained upon CuO loading [48]. …”
Section: Metal-support Interactionssupporting
confidence: 59%
“…to 145 cm −1 in CuO-TiO2 NTs can be attributed to the presence of oxygen vacancies [24,45,46]. The CuO modification resulted in changes in the structural and vibrational properties of the TiO2 lattice, which indicates the strong interaction between the CuO and TiO2 NTs support [35,[46][47][48]. The position of the Raman peaks associated with the B1g and A1g vibration modes of TiO2 was influenced by the CuO modification in CuO-TiO2 NTs compared to pristine TiO2 NTs, as can be seen in Figure 7b.…”
Section: Metal-support Interactionsmentioning
confidence: 99%
“…The Ti-O-Ti network bands in the region 400-700 cm -1 are characteristic of anatase and rutile structure. Typically, three Raman active fundamental modes for anatase phase are appeared at 397cm -1 (B1g), 518 cm -1 (A1g+ B1g) and 640 cm -1 (Eg) and rutile TiO2 at 613 cm -1 (A1g) [34]. Furthermore, the band at 144 cm -1 shifted towards higher wave number (inset Figure 4(i)), while the 640 cm -1 peak drifted downwards to lower wave number (inset Figure 4(ii)) is presumably due to the interaction of mono and/or bi metallic species with TiO2 [35].…”
Section: Raman Spectroscopic Analysismentioning
confidence: 99%
“…Metals with a lower Fermi energy level than that of TiO2 can trap and transfer the photo-excited electrons from the conduction band to reduce protons into H2, while the holes remain in the valence band 5 . It is already found that the creation of oxygen vacancies and the formation of rutile seeds embedded into an anatase structure could be responsible for this improved photoactivity 6 . For TiO2 system, the formation of this particular structure could favor the electron trapping and diffusion process, avoiding the recombination process 7 .…”
Section: Introductionmentioning
confidence: 99%